Transformasi Bentuk dan Rupa Rumah Niang Mengkini dengan Konsep Ikonik dan Pendekatan Arsitektur Nusantara - Marianne Tunggadewi Juluk Dwiputri (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
The presence of Indonesian architecture in an area can show the identity and character of cultural and traditions of these place. The distinctive characteristics of Manggarai architecture in the city of Labuan Bajo, West Manggarai district are very necessary to show the identity and genius locus of the Manggarai people in the field of architecture as well as a form of preserving traditional Manggarai houses which are almost extinct due to the influence of modernization. In creating a contemporary Indonesian building that departs from the character of the niang house, a design strategy is needed that is able to depict traditional Manggarai architecture in the form of contemporary Indonesian architecture while still paying attention to the function and location of the design. The aim of this research is to produce a contemporary Indonesian architectural design strategy that can be used in various functions and locations. The design method used is Rob Krier's geometric transformation method and Broadbent's iconic concept with an Indonesian architectural approach. The design results are a resort hotel design strategy with the shape and appearance of today's niang houses located on Pede Beach, Labuan Bajo City, West Manggarai Regency, NTT Province.